Automated discovery of scientific concepts: Replicating three recent discoveries in mechanics. (April 2020) - Hakuk, Yaron; Reich, Yoram
Highlights: Filling the hole approach is a general discovery strategy. Knowledge-based knowledge discovery. Replicating automatically the discovery of new concepts and methods in mechanics. Automated scientific discovery by transferring knowledge between disciplines. Abstract: Throughout history, humanity cherished new scientific discoveries; many people devoted their lives to find them in laborious manual processes. Since the emergence of artificial intelligence, about 60 years ago, the possibility of automated scientific discovery has become conceivable and has attracted significant and growing interest. Many studies of automated scientific discovery have been presented over the years. This article presents a new automated discovery approach that crosses disciplines and transfers knowledge between them. The approach requires rich and formal background knowledge to find concepts, methods, or laws not known in one discipline by using their counterpart in other disciplines, specifically disciplinary knowledge that is represented in the Interdisciplinary Engineering Knowledge Genome. Three recent discoveries in mechanics were replicated automatically through software execution, demonstrating the validity of the approach. In future studies, the goal is to discover new knowledge in mechanics and/or electronics, as well as venture into other disciplines including outside engineering.